Maternal and perinatal outcomes in women with polycystic ovarian syndrome - Hoque, Luna Farhana; Zinan, Aklima Zakaria; Apsara, Suraiya; Danny, Afreen Sultana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Pregnant individuals with polycystic ovarian syndrome (PCOS) seem to face a heightened susceptibility to unfavorable outcomes. This investigation aimed to evaluate the consequences of pregnancies in patients diagnosed with PCOS. Methods: This cross-sectional study involving 115 pregnant patients with PCOS was carried out at the department of obstetrics and gynecology, Dhaka medical college and hospital, Dhaka, Bangladesh, tertiary care facility, from January 2023 to December 2023. Data on the ongoing pregnancy, PCOS, and outcomes were analyzed by SPSS version 20. Results: Average age of participants was 25.07 years. Incidence of premature rupture of membranes (PROM) was 33.91%, low APGAR score at 5 minutes was 12.17%, gestational diabetes (GDM) occurred in 23.47% of cases, miscarriage was reported in 2.1%, preterm delivery in 13.91%, cesarean delivery in 37.39%, low birth weight babies accounted for 2.6%, macrosomia occurred in 0.7%, preterm PROM (PPROM) in 19.52%, perinatal mortality 1.73%. Conclusions: In pregnancy with PCOS, the percentage of GDM, preterm delivery, meconium-stained liquor, small for gestational age (SGA)/intrauterine growth restriction (IUGR), macrosomia, PPROM, perinatal mortality, neonatal intensive care unit (NICU) admission, and congenital anomalies were either comparable or lower. However, a higher percentage of hypertension in pregnancy, PROM, low birth weight babies, and low APGAR score at five minutes was observed in this population.